A new method of integrating project‐based and work‐integrated learning in postgraduate engineering study. Issue 1 (20th December 2019) - Karim, Azharul; Campbell, Matthew; Hasan, Mahbub
Abstract : This paper reflects on the introduction of project‐based learning (PBL) into a postgraduate engineering management unit, as a form of work‐integrated learning (WIL) extending the practice of students and their engagement with industry. The real life and authentic PBL was designed and implemented in extensive consultation with industry practitioners. WIL has often been conceptualized as a process of induction and introduction to workplaces and work practices. However, such models do not easily translate to postgraduate students with existing workplace experiences. The experience of this unit suggests that there is an intersection between PBL and WIL which may provide a pathway for broader student–industry engagement, scaffolding the development of professional networks and practices for students already within an engineering workplace, and allowing students to transform their practice and improve workplace capabilities. This paper presents a case study of the experience of students who have participated in an industryled and assessed project based learning experience as part of a unit in the Masters of Engineering Management course. Student satisfaction and engagement with the unit was extremely high, with students self‐reporting increased levels of confidence and ability to apply theoretical knowledge. It is concluded that through the integration of project‐based and WIL it is possible to create authentic learning experiences for postgraduate students which enable transformative practice and capability development.